ANALYSIS AND MEASUREMENT OF THE IMPACT OF FOREIGN DIRECT INVESTMENT ON THE GROSS DOMESTIC PRODUCT IN IRAQ FOR THE PERIOD 2004-2022 - Susan Fawaz Abdel-Wahhab al-Dabbagh (American Journals, 2023)
The research aims to measure and analyze the resulting impact on foreign direct investment through the solutions that must be taken in a positive way for economic development in Iraq. model explanatory (R2 = 0.872016), and the value of D-W was (2.023146), meaning that the model is devoid of correlation. The F-statistic value also reflected the significance of the model as a whole, which is less than (5%). The short-term results showed that foreign direct investment as an independent variable has succeeded in proving its significant and positive impact on the GDP index (Y1), but in the long term, if (investment Foreign Affairs) has succeeded in stabilizing its positive and moral impact in the indicator of the local product, and the research is recommended to the decision maker the field of the field for the foreign investment. And fighting the administrative and financial corruption, working to achieve stability and stopping conflicts and conflicts Political and partisan quotas, since these matters are among the determinants of the investment climate, in addition to rationalizing unnecessary government spending and directing it towards the construction of infrastructure.
Keywords: Foreign direct investment, gross domestic product